3x+2(-2x-4)=-4

Simple and best practice solution for 3x+2(-2x-4)=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+2(-2x-4)=-4 equation:


Simplifying
3x + 2(-2x + -4) = -4

Reorder the terms:
3x + 2(-4 + -2x) = -4
3x + (-4 * 2 + -2x * 2) = -4
3x + (-8 + -4x) = -4

Reorder the terms:
-8 + 3x + -4x = -4

Combine like terms: 3x + -4x = -1x
-8 + -1x = -4

Solving
-8 + -1x = -4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + -1x = -4 + 8

Combine like terms: -8 + 8 = 0
0 + -1x = -4 + 8
-1x = -4 + 8

Combine like terms: -4 + 8 = 4
-1x = 4

Divide each side by '-1'.
x = -4

Simplifying
x = -4

See similar equations:

| 30x+40=7x+34 | | 3x-7=x+41 | | 4(3x+2)-x=8x-8 | | 7(g-3)+5g= | | 3=4x^(2/5) | | h-6u+7=-29 | | 6=2k-8k | | E(x)=0.0048x^3-0.0054x^2 | | 7(x-6)=5(x+2) | | 6b^2=42b-72 | | 7(8-9x)=0 | | 3x+9-5x+7-2x=20 | | 7y+45=y-3 | | -x+21=x+9 | | a-17=48 | | 3b-3=9 | | (4x+8)-(2x+4)=2x | | 2x+5(5x-1)=-113 | | 10(c-7)=-36 | | 7/9-= | | 5y/9=45 | | (4x+6)-(2x+4)=2x | | 9x(x+9x)= | | -4.5n+3= | | 3y+20=14 | | 12s-24=0 | | 2(y+1)-5=-15 | | 4j-36=0 | | 8-41=40 | | 4k-42=-1 | | 6+4r=2(r-4) | | 4h-42=-18 |

Equations solver categories